2018
DOI: 10.1111/spsr.12290
|View full text |Cite
|
Sign up to set email alerts
|

The Making of the Informed Voter: A Split‐Ballot Survey on the Use of Scientific Evidence in Direct‐Democratic Campaigns

Abstract: Literature claims that scientific evidence makes better democracies. This paper analyses whether and which voters choose empirical evidence in the form of policy evaluation results when informing themselves about issue‐specific votes. The analysis is based on a split‐ballot survey where participants chose media items with different content to make a decision on a specific issue. Results show that voters do indeed choose evidence‐based information, especially if their involvement with the issue is high and if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…Especially when it comes to direct democracy, citizens should be well informed about different positions and current events regarding the policy in question ( Stucki et al, 2018 ). The results from this study indicated that high amounts of referendum campaign coverage did not only have positive effects, as assumed by previous research ( Dvořák, 2013 ; Hobolt, 2005 ; Leduc, 2002 ), but also detrimental effects on citizens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially when it comes to direct democracy, citizens should be well informed about different positions and current events regarding the policy in question ( Stucki et al, 2018 ). The results from this study indicated that high amounts of referendum campaign coverage did not only have positive effects, as assumed by previous research ( Dvořák, 2013 ; Hobolt, 2005 ; Leduc, 2002 ), but also detrimental effects on citizens.…”
Section: Discussionmentioning
confidence: 99%
“…. This is particularly important during a referendum when citizens accept or reject a specific policy (Stucki et al, 2018) rather than vote on political representatives. Thus, citizens' knowledge about the policy issue has direct effects on their voting decision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In times of unusual social tensions caused by the political struggle with relatively high stakes, the proliferation of false news, misinformation and other sorts of media manipulation is to be expected. The importance of voter competence is one of the postulates of modern democracy [61,62] and information vacuums can undermine electoral accountability [63]. An ideal democracy assumes an informed and rational voter, but the former aspect is something that can be undermined or compromised.…”
Section: Misinformation and 2020 Us Presidential Electionmentioning
confidence: 99%
“…coined the term intelligent democracy, a democracy in which free access to scientific evidence provides for an informed public discourse. Such an evidence-based discourse is especially relevant in direct-democratic campaigns where political actors aim to convince citizens to oppose or support a policy through arguments (Stucki et al 2018;Sager et al 2017b;Sager 2017). To this end, political actors frame their arguments, that is, "they select some aspects of a perceived reality and make them more salient in a communicating text" (Entman 1993: 52).…”
Section: Introductionmentioning
confidence: 99%